2011
DOI: 10.1016/j.annepidem.2011.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Yard Flooding by Irrigation Canals Increased the Risk of West Nile Disease in El Paso, Texas

Abstract: Purpose To investigate the effects of use of water from irrigation canals to flood residential yards on the risk of West Nile disease in El Paso, Texas. Methods West Nile disease confirmed cases in 2009–2010 were compared with a random sample of 50 residents of the county according to access to and use of water from irrigation canals by subjects or their neighbors, as well as geo-referenced closest distance between their home address and the nearest irrigation canal. A windshield survey of 600 meters around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Although 271 human cases of WN were reported annually between 2003 and 2016 in El Paso Texas, serosurveys have not been conducted to determine estimates of WNV IgG antibody as evidence of past infections in the population [ 19 , 78 ]. Our serosurvey provided further evidence of WNV human infection in the El Paso community, but was focused on rates among child-bearing age females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although 271 human cases of WN were reported annually between 2003 and 2016 in El Paso Texas, serosurveys have not been conducted to determine estimates of WNV IgG antibody as evidence of past infections in the population [ 19 , 78 ]. Our serosurvey provided further evidence of WNV human infection in the El Paso community, but was focused on rates among child-bearing age females.…”
Section: Discussionmentioning
confidence: 99%
“…The first WN human cases were reported during 2003 in El Paso, Texas, where Culex quinquefasciatus and Culex tarsalis are the primary vectors [16,18]. Estimates based on passive surveillance in El Paso indicated that 271 cases of WN occurred between 2003 and 2016, with cases occurring during late June to early November, and peaking in August during each year [17,19] Although DENV have not been reported to be associated with human infections and/or disease in the El Paso community, such cases and/or infections may not have been detected because of the reliance on passive surveillance to detect symptomatic cases. As an example, the use of passive surveillance during a 1980 dengue outbreak in Brownsville, TX failed to detect any dengue cases in El Paso, but 63 cases were detected by active surveillance.7 Another possibility for not detecting human cases is because DENV, like most arboviruses more commonly cause asymptomatic infections or infections that cause a mild influenza-like illness [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in El Paso, Texas, where Cx. tarsalis is the primary vector, WNV case-patients were close to yards that were flooded regularly by irrigation canals (35). In northern Colorado, where Cx.…”
Section: Risk Factors For Populationsmentioning
confidence: 99%
“…The pattern of prevalence of waterborne diseases such as typhoid fever, cholera, leptospirosis, diarrheal diseases, and hepatitis appears to have changed after the flood (2)(3)(4). The prevalence of not only waterborne diseases but also vectorborne diseases such as malaria, West Nile fever, and dengue fever has increased after the flood (5,6).…”
Section: Introductionmentioning
confidence: 99%